Productive vocation and territorial productive reality: the case of the province of Arauco, Chile, 2021 - Esau Figueroa Silva; Javier León-Aravena (Población y Desarrollo, 2023)
The territorial productive vocation, conceived as the set of aptitudes, dispositions and productive potentialities that the inhabitants of a territory present, is a relatively little explored area of work and provided with important development potentialities, being interesting to study its concepts in contexts provided with economic, social and/or environmental contradictions. For this, the case of the Province of Arauco, in Chile, is proposed, a territory classified as a lag economic area due to its problems of poverty and connectivity, even when it houses one of the most important productive activities in the country, such as the forestry industry. In this way, the present article aims to explore the productive vocation present in the Province of Arauco and its relationship with the productive reality present there. The work is carried out with a qualitative approach, based on secondary data contained in the Communal Development Plans of seven communes of the territory, analyzing the visions, missions, objective images and objectives of productive development. The main finding is the identification of a mismatch between the large-scale productive structure (forestry) and the territorial productive vocation (oriented to sustainable local tourism). We conclude that this helps to explain the persistence in indicators of poverty, exclusion and vulnerability in this province. The study is limited by the characteristics of the instruments studied, while its originality lies in this.